A Rapid and Sensitive Detection Method for Pseudomonas aeruginosa Using Visualized Recombinase Polymerase Amplification and Lateral Flow Strip Technology - Yang, Haitao; Wang, Yan; Yang, Qiankun; Fan, Hui; Wang, Lei; Zhang, Tianmeng; Li, Zhixing; Liu, Gang; Zhao, Panpan; Wu, Huahua; Dong, Jingquan; Liang, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa is a common opportunistic pathogen that causes acute nosocomial necrotizing pneumonia and is the predominant source of chronic lung infections in patients with the genetic disorder cystic fibrosis. Early diagnosis in infected patients and monitoring P. aeruginosa contamination is therefore of great importance in controlling disease spread and development with timely drugs intervention treatment and cut off infection source. Traditional culture-biochemical methods are time consuming and highly dependent on technicians and expensive instruments. To address these challenges, the present study aimed to develop a rapid, sensitive, and specific, on-site detection method for P. aeruginosa based on recombinase polymerase amplification (RPA) combined with lateral flow strip (LFS) technology. The experimental process included screening and modification of primer and probe sets targeting the unique virulence gene elastase B (lasB); specificity detection in 29 strains of P. aeruginosa and 23 closely-related pathogenic bacteria; sensitivity measurements with gradient-diluted P. aeruginosa genomic DNA and probit regression analysis; and clinical application evaluation using 574 patients samples and calculating coincidence rate and kappa index value in comparison with the culture-biochemical method. The P. aeruginosa RPA-LFS assay could complete the amplification process at 37°C constant temperature within 30 min and results could be visualized by the naked eye within 10 min on LFS. The assay displayed high sensitivity with a limit of detection of 3.05 CFU/reaction. It also demonstrated high specificity by showing no cross reaction with other pathogenic bacteria, and rapidness by being completed in less than an hour. Furthermore, when used with clinical samples, the assay had a coincidence rate of 98.26% with the culture-biochemical method and a kappa index value of 0.9433. These data indicate that the RPA-LFS assay represents a major improvement for P. aeruginosa detection, especially in resource-limited areas.